PERFORMA PRAGMATIK ANAK USIA TIGA TAHUN DARI BERAGAM LATAR BELAKANG SOSIAL - Yesika Maya Ocktarani (Universitas Muhammadiyah Semarang, 2013)
In our society, child language development is usually identical with the amount of newvocabularies produced by a child. Yet, in preparing a child to get involved with his or hercommunity, parents should also consider childs pragmatic competence. This paper is aimedto give perspective about childrens pragmatic competence particularly on their performancein Directive Speech Acts (DSA) and also to describe their environment which supports theirpragmatic performance. Using qualitative descriptive method, researcher involves fourchildren who have different social background. Direct observation is used in order to get datanaturally and it is also completed by in-depth-interview with childrens parent and teacher.The result shows that 3-year-old children are able to understandand to produce DSA. Theirability in understanding DSA can be seen when they respond ones DSA, both verbally andnon-verbally. In producing DSA, they use indirect form to express their intention. Anotherresult of this research is that children should have linguistic environment to stimulate theirability in using language as tools of communication. The more children interact verbally witha speech community, the better their pragmatic competence will be.Keywords: Directive Speech Acts, three-year-old children, linguistic environment